Domain conditions in social choice theory - Gaertner, Wulf (Cambridge University Press, 2001)
Offering the most comprehensive and up-to-date survey of current research in an important area of social choice theory, Wulf Gaertner's monograph provides an essential reference for economists and political scientists. In the interests of accessibilty and readability, extensive formal proofs to theorems are not included in the text but are carefully referenced, allowing interested readers to pursue them independently. Though written in a formal style, the mathematical level of the book is designed to be appropriate for graduate students with a basic training in mathematics